2017
DOI: 10.2166/ws.2017.225
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for the removal of benzene, toluene, ethyl benzene and xylene (BTEX) from aqueous solutions using iron nanoparticles

Abstract: Magnetic nanosorbents proved to be highly effective in inorganic and organic contaminants removal from aqueous solutions, especially nano zero valent iron (nZVI). The main purpose of this study is to investigate the effect of using nZVI in removing benzene, toluene, ethyl benzene and xylene (BTEX) contaminants from aqueous solutions. The nZVI and the standard BTEX solution were prepared in the laboratory. X-ray diffraction (XRD), UV spectrophotometry, and scanning electron microscopy (SEM) analysis were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Many researchers have focused on developing new methods using nano-catalysts technology to overcome these limitations (Mahmoud et al 2018b;Abdel-Gawad et al 2016;Farag et al 2018a, b). Since the 1990s, iron nanoparticles (FeNPs) have been used to treat water because of its characteristics viz.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have focused on developing new methods using nano-catalysts technology to overcome these limitations (Mahmoud et al 2018b;Abdel-Gawad et al 2016;Farag et al 2018a, b). Since the 1990s, iron nanoparticles (FeNPs) have been used to treat water because of its characteristics viz.…”
Section: Introductionmentioning
confidence: 99%
“…Second, at high acidic media, the small amount of metal was dissolved by the effect of acid leading to losing a huge number of vacant sites and that affected the adsorbent dose capacity. 2 The high alkaline solution with an excess of OH − ions effects on adsorption activities of nZVmetal through the steric effect of negative charge. 48,49 There are different studies conducted with COD removal using different sorbent materials and showed that the effective pH values ranged from 7.5 to 8 showing agreement of the obtained resu lts.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Equation (1) describes the reaction of nano zero-valent iron when contacted with the aqueous solution indicating that the electron transfer process is responsible for its reactivity. 19,20 Also, previous studies describe that nZVAl have a similar character for degradation and adsorption of wide range of wastewater contaminants as in equations (2) and (3). 21 The selection of alternative high-efficiency zero-valent metals depends on the facility of electron transfer and the stability of dissolved metals against precipitation through different pH ranges.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nanoparticles play a serious role in contaminants removal from the aquatic surroundings (Tatarchuk et al., 2019, 2020a, 2020b). In current years, nanoscale particles prepared by NaBH4 (Mahmoud, 2017; Mahmoud et al., 2018a; SaryEl-deen et al., 2017), but they cause major contamination. It is critical to find alternate, low-cost, ecologically friendly techniques (Zhu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%